A bibliometric analysis of the past 25 years at International Journal of Geographical Information Science - Quesada Román, Adolfo (2024)
The article provides a comprehensive analysis of the evolution and impact of the International Journal of Geographic Information Science (IJGIS) over the past 25 years. IJGIS, the first journal exclusively dedicated to Geographic Information Science (GIS), has significantly expanded its publication output to meet the growing demand for GIS research. Utilizing conceptual science mapping analysis, the study traces the thematic evolution of the journal by collecting scientific papers from the Web of Science database from 1997 to 2021. Bibliometric performance indicators were employed to highlight its influence and thematic development. The primary themes covered include error modeling, digital elevation models, simulation, conservation, and land-use change. Furthermore, IJGIS has broadened its scope to include emerging topics such as volunteered geographic information, the integration of big data techniques, and artificial intelligence. Geographically, contributions are predominantly from the USA, followed by China and the UK, underscoring the journal’s international recognition and impact. Compared to global averages, IJGIS consistently maintains a high normalized impact within its thematic area. In conclusion, IJGIS has undergone significant evolution, adapting to GIS field changes, and expanding its global influence with prospects for further diversification and technological integration.